Health Literacy Influences Men's Active and Passive Cancer Information Seeking - Frances J. Drummond; Mary Reidy; Christian Von Wagner; Vicki Livingstone; Jonathan Drennan; Mike Murphy; Colin Fowler; Mohamad M. Saab; Mairin O'Mahony; Josephine Hegarty (SLACK Incorporated, 2019)
Background: For cancer prevention information to be effective, it must be accessible to its target populations. Prevalence of inadequate health literacy (HL) is high, but there is a dearth of information on the impact of HL on men's cancer information seeking. Objective: We investigated (1) men's cancer information seeking behaviors, (2) the effect of HL on men's cancer information seeking behavior, and (3) men's preferences for cancer information, considering their HL level. From a national perspective, we investigated men's information seeking behavior from the Irish Cancer Society (ICS), the largest provider of cancer information in Ireland. Methods: Men from adult literacy classes and men's groups were invited to complete a questionnaire. General and ICS-specific cancer information seeking behavior was investigated. Univariate and multivariate logistic regression models were conducted with "ever" seeking cancer information from any source, and actively seeking and passively acquiring ICS information as dependent variables. Key Results: Overall, 259 men completed the questionnaire and 44% had inadequate HL. About one-half of responders reported "ever" actively looking for cancer information. In the study group, 19% actively sought and 67% passively acquired ICS-specific information. In multivariate analysis, the odds of actively seeking (2.93; 95% CI [1.05, 8.15]) or passively acquiring (4.7; 95% CI [1.99, 11.05]) ICS-specific cancer information was significantly higher among those with adequate versus inadequate HL, respectively. HL was not significantly associated with odds of "ever" cancer information seeking in multivariate analysis (odds ratio 1.81; 95% CI [0.90, 3.63]). Men want information about cancer prevention. Suggested future cancer information sources differed by HL levels. General practitioners and the Internet were the preferred source for men with inadequate (53.3%) and adequate HL (57%), respectively. Conclusions: Men both passively acquire and actively seek cancer prevention information. Multimodal dissemination of cancer prevention information is necessary to reach a wide cross-section of men, including those with inadequate HL. This could potentially lower men's cancer burden and reduce gender inequalities in cancer mortality.